Scalable Domain Decomposition Algorithms for Simulation of Flows Passing Full Size Wind Turbine (Communications in Computational Physics, 2018)
Accurate numerical simulation of fluid flows around wind turbine plays animportant role in understanding the performance and also the design of the wind turbine.The computation is challenging because of the large size of the blades, the largecomputational mesh, the moving geometry, and the high Reynolds number. In thispaper, we develop a highly parallel numerical algorithm for the simulation of fluidflows passing three-dimensional full size wind turbine including the rotor, nacelle,and tower with realistic geometry and Reynolds number. The flow in the moving domainis modeled by unsteady incompressible Navier-Stokes equations in the arbitraryLagrangian-Eulerian form and a non-overlapping sliding-interface method is used tohandle the relative motion of the rotor and the tower. A stabilized moving mesh finiteelement method is introduced to discretize the problem in space, and a fully implicitscheme is used to discretize the temporal variable. A parallel Newton-Krylovmethod with a new domain decomposition type preconditioner, which combines anon-overlapping method across the rotating interface and an overlapping Schwarzmethod in the remaining subdomains, is applied to solve the fully coupled nonlinearalgebraic system at each time step. To understand the efficiency of the algorithm,we test the algorithm on a supercomputer for the simulation of a realistic 5MW windturbine. The numerical results show that the newly developed algorithm is scalablewith over 8000 processor cores for problems with tens of millions of unknowns.